2002
DOI: 10.1098/rspb.2002.2147
|View full text |Cite
|
Sign up to set email alerts
|

A plant pathogen reduces the enemy–free space of an insect herbivore on a shared host plant

Abstract: An important mechanism in stabilizing tightly linked host-parasitoid and prey-predator interactions is the presence of refuges that protect organisms from their natural enemies. However, the presence and quality of refuges can be strongly affected by the environment. We show that infection of the host plant Silene latifolia by its specialist fungal plant pathogen Microbotryum violaceum dramatically alters the enemy-free space of a herbivore, the specialist noctuid seed predator Hadena bicruris, on their shared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 46 publications
0
46
0
1
Order By: Relevance
“…In our study, larval mass at emergence from aborted fruits was less than half the mass of larvae emerging from nonaborted fruits. Leaving earlier and at smaller size from the primary fruit implies increased risks, since the primary fruit grants protection from parasitoids (Awmack and Leather 2002;Benrey and Denno 1997;Biere et al 2002). At least 14 parasitoid species have been described from H. bicruris larvae (Elzinga et al 2007), most of which attack the larvae at instar L4 or L5 (Elzinga et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, larval mass at emergence from aborted fruits was less than half the mass of larvae emerging from nonaborted fruits. Leaving earlier and at smaller size from the primary fruit implies increased risks, since the primary fruit grants protection from parasitoids (Awmack and Leather 2002;Benrey and Denno 1997;Biere et al 2002). At least 14 parasitoid species have been described from H. bicruris larvae (Elzinga et al 2007), most of which attack the larvae at instar L4 or L5 (Elzinga et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Fungal attack reduces the benefits of the interaction to the moth. It is interesting that this is mediated not only by reduced resource quality of infected plants, but also by reduced 'refuge space' for moth larvae (Biere et al, 2002), a factor known to be important in stabilizing trophic interactions in natural communities. Moths respond by avoiding oviposition on infected plants (Biere and Honders, 2006).…”
Section: G Bernasconi Et Almentioning
confidence: 99%
“…Several studies have further demonstrated that rate of parasitism of a herbivore is affected by plant pathogens (Biere et al 2002;Cardoza et al 2003), and that host plant quality can affect parasitoid population dynamics (i.e. van Nouhuys & Hanski 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Very little is known about the effects of fungal phytopathogens on trophic levels above insect herbivores, despite the great abundance and diversity of plant pathogens (Ingram & Robertson 1999). The few studies that have been conducted show high parasitism of herbivores feeding on fungal-infected plants, due to changes in plant structure (Biere et al 2002) or composition of volatile emissions (Cardoza et al 2003). Endophytic infection, though not detrimental to the host plant, also alters plant physiology.…”
Section: Introductionmentioning
confidence: 99%